Vivências de sobreviventes ao suicídio de jovens: impacto na vida dos enlutados. - Gomes, Eliene Rocha (2019)
Suicide, a multicausal and complex phenomenon, is the third leading cause of death among young people in Brazil and worldwide. It is estimated that for each suicide, about 6 to 10 people are impacted by this death. Suicide for suicide differs from others in that it is characterized by a sudden, unnatural and desired death. Survivors - that is, people who are affectionately close to the person who committed suicide and who experience high psychological, physical or social distress following exposure to another person's suicide - have to deal with the loss of the person with the fact that this type of death be the target of prejudice and stigma, historically and socially constructed. This study aimed to analyze aspects of survivors' bereavement experiences, specifically the process and elaboration of mourning, as well as the impact of suicide on their daily lives. A qualitative descriptive and exploratory research was conducted through narrative interview. The choice for this type of interview was due to the participant's use of his own terms, given the delicate subject, with strong component of pain. Seven survivors, including friends and family members of young people aged 15 to 24 who committed suicide participated. After the thematic analysis of the content of these interviews, three meaning cores were indicated and discussed: Grief Process; Elaboration of mourning; Suicide and subjective changes. In the process experienced by the participants, when they came in contact with the loss of young people due to suicide, they narrated about the description of the young person, about the last contact and about the description of feelings about the loss. In the process of elaboration of grief, the survivors presented, in their narratives, the pain and sadness that indicate propensity to some forms of psychological distress. In addition, they presented a movement to look for causes and blame other people for what happened, often with expressed anger directed at them. Also part of this process was the attempt to understand through rationalized explanations, creating a distance between the event and themselves. Completing the narrative of this grief task, the survivors reported their support for this process of overcoming. We highlight the engagement in concrete actions of the survivor resulting from the experience of suicide of a young affectionately close, important in his life. In relation to suicide and subjective changes, we find reports that indicate the elaboration of grief through the transformation of pain and feelings caused by suicide into something socially accepted, that is, they use / refer to the pain experienced with loss at work. with other people. The changes in attitudes toward life toward the youth's pre-suicide life reported by the survivors were: taking back / valuing one's own life and being alert, available, to help the other. We conclude that losing someone by suicide is an experience that carries the traumatic in its different expressions, often marked by intense suffering. These are survivors who, even in the face of such pain, also experienced psychological growth, resignification of their own life and overcoming.